Assessment of interleukin -10 and interferon-gamma with oral squamous cell carcinoma patients compared with healthy subjects as a prediction for early detection and monitor treatment response (Mustansiria Dental Journal, 2024)
Background:  In the worldwide oral squamous cell carcinoma (OSCC) is considered to be one of the most deadly diseases, due to it is late in diagnosis and absence of availability of established reliable biomarkers. The aim of current study was designed to detect cytokines in saliva of patient with oral squamous cell carcinoma and compared their levels with the healthy subjects and evaluate their validity as diagnosis and investigated changes of cytokines level in saliva pre-and post- surgical treatment to provide knowledge for exploring the use of saliva to monitor treatment response.Material and method: whole unstimulated saliva was collected from each individual (25 OSCC patients Pre- and post- surgical removal of tumor and 25 healthy individuals matching with age and gender as control group. saliva was evaluated both cytokines IL 10 and interferon gamma by ELISA.Result: IL-10 level is increased significantly in group of OSCC patients compared to healthy subjects (control group). Ten days after surgical removal of tumor, salivary level IL10 was decreased significantly in comparison to its level pre-operation. In OSCC patients salivary level interferon gamma was decreased significantly than its level in healthy subjects, ten days after surgical removal of tumor salivary level interferon gamma was increased significantly in group of OSCC patients in comparison to their level before surgical removal of tumor.Conclusion: salivary levels of both cytokines IL-10, and interferon gamma could prove to be potential biomarkers of OSCC.